Synopsis Methodica Molluscorum by C. T. Menke - William J. Clench (Hello World!, 1969)
Two editions of this work by Menke appeared, the first in 1828 (Pyrmont, Germany, 12 + 91 pp. ) and the second, 'Editio altera,' in 1830 (Pyrmont, Germany, 16 + 168 pp.). Both gave a list of species contained in his collection as well as descriptions of many new species. In the second edition, many additional species were described; unfortunately nearly all of the species which appeared in the 1830 edition were republished as new in the 1830 edition.